A colloidal model system with tunable disorder: Solid-fluid transition and discontinuities in the limit of zero disorder - Richter, Christian; Schmiedeberg, Michael; Stark, Holger (European Physical Journal E, 2011)
We study a colloidal model system where disorder can be continuously tuned from no disorder-corresponding to a system that can crystallize-to large disorder where geometrical frustration occurs. The model system consists of colloidal particles with screened electrostatic repulsion. They can only move on single lines which are parallel and equidistant to each other. We introduce disorder by modulating the particle line density. The system exhibits a solid-to-fluid transition which we study by the structure factor and the temporal evolution of the mean-square distance of nearest neighbors on neighboring lines. A determining feature is the occurrence of discontinuities when disorder is tuned to zero. We observe that the peak height of the pair correlation function in the solid phase does not extrapolate to the value of the perfect crystal. Similarly, the mean interaction energy and the screening length at which the solid-fluid transition occurs seem to be discontinuous when the limit of zero disorder is approached.